Damage of prismatic lithium‐ion cells subject to bending: Test, model, and detection. Issue 6 (17th July 2022) - Li, Wei; Xing, Bobin; Watkins, Thomas R.; Xia, Yong; Wang, Hsin; Zhu, Juner
Abstract: The mechanically induced internal short circuit (ISC) is one of the major safety concerns of lithium‐ion batteries. Mechanical abuse tests are often performed to evaluate the integrity and safety of lithium‐ion batteries under mechanical loadings. Except for the widely explored compression‐dominated indentation tests, bending is another typical real‐world loading condition that is tension‐dominated. To investigate the mechanical damage and ISC behavior of batteries under bending, we carried out controlled three‐point bending tests in four progressive steps on prismatic battery cells with maximum deflections ranging from 38% to 76% of the cell thickness. None of the tested cells experienced an ISC. We then conducted 3D X‐ray computed tomography (CT) scanning on the bent cells after unloading. X‐ray CT images showed three out of the four tested cells have extensive cracking in the electrode layers at the bottom side (opposite to the loading head). This indicates that cracking does not necessarily lead to an ISC under bending. Electrochemical impedance spectroscopy was also measured on the bent cells and substantial changes were observed. Both the bulk resistance and charge‐transfer resistance increased significantly after bending, which could influence the battery performance and lifespan. We then developed a detailed finite (FE) element model to further investigate the mechanical deformation and failure mechanisms. The FE model successfully predicts the load–displacement response and reproduces the deformation patterns. The findings and the FE model developed in the present study provide useful insights and tools for the battery structure and crash safety design. Abstract : Testing and modeling of three‐point bending on small format prismatic cells are performed. X‐ray CT scanning, together with a high‐fidelity Finite Element model, has revealed the delamination and cracking of electrodes inside bent cells under deflections greater than 38% of the thickness. While internal short circuit is not detected, the impedance behaviors are largely impacted.